Levels of Involvement with Child Protection Services Associated with Early Adolescent Police Contact as a Victim and Person of Interest - Tzoumakis, Stacy (Journal of interpersonal violence, 2024)
The relationship between childhood maltreatment and subsequent offending/victimization is well established. However, the magnitude of this relationship for different levels of child protection services (CPS) involvement is poorly understood, due to measurement issues, lack of longitudinal data, and reliance on reports of substantiated maltreatment, which can underestimate the impact of maltreatment. This study examined associations between CPS involvement during childhood (ages 0 to <11 years) and police services contact (as a victim and/or a person of interest) for criminal incidents in early adolescence (11 to ~14 years), differentiated according to levels of CPS involvement (i.e., no risk of significant harm [non-ROSH], unsubstantiated ROSH, substantiated ROSH, and out-of-home care; each examined relative to no CPS contact). Data for 71,465 children were drawn from the New South Wales Child Development Study, an intergenerational, longitudinal investigation that uses administrative records from CPS and police alongside other health, justice, and education data. Multinomial regression analyses were conducted to determine associations between increasing levels of CPS involvement and police contact as a victim only, a person of interest only, and as both victim and person of interest while accounting for covariates (i.e., child’s sex, Aboriginal, and/or Torres Strait Islander background, socioeconomic status, maternal age at child’s birth, and parental offending history). Children exposed to any of the four levels of CPS involvement had higher odds of police contact, relative to children with no CPS involvement. Odds ratios were higher for contact with police as both a victim and a person of interest, compared to police contact as a victim or a person of interest only. These findings highlight that children with even unsubstantiated CPS reports (i.e., non-ROSH and unsubstantiated ROSH reports) are at heightened risk of police contact compared to children who are unknown to CPS, underlining the need to support all families in contact with CPS.